Lung function in the late postoperative phase and influencing factors in patients undergoing pulmonary lobectomy - Matsumoto, Ryoichi; Takamori, Shinzo; Yokoyama, Shintaro; Hashiguchi, Toshihiro; Murakami, Daigo; Yoshiyama, Koichi; Nishi, Tatsuya; Kashihara, Masaki; Mitsuoka, Masahiro; Hayashida, Ryozo; Kakuma, Tatsuyuki; Akagi, Yoshito (Journal of Thoracic Disease; Vol 10, No 5 (May 31, 2018): Journal of Thoracic Disease, 2018)
Background: Lung function in the late postoperative phase after pulmonary lobectomy is insufficiently characterized. This study aimed to appraise lung function in the late postoperative phase according to vital capacity (VC) and forced expiratory volume in 1 second (FEV1) in patients who underwent pulmonary lobectomy. Methods: Pre- and postoperative VC and FEV1 were reviewed in 112 patients who underwent pulmonary lobectomy. Postoperative lung volume was assessed >1 year after surgery. Postoperative decreases in VC and FEV1 were compared with preoperative predicted values among patients who underwent resection of specific lobe. Determinants effecting a decrease in lung function were also investigated. Results: A mean postoperative decreased VC of 10.5%±1.8% was recorded in patients who underwent right upper lobectomy (RU), 7.2%±1.5% for right middle lobectomy (RM), 14.3%±2.3% for right lower lobectomy (RL), 16.6%±3.0% for left upper lobectomy (LU), and 14.7%±2.5% for left lower lobectomy (LL). Corresponding FEV1 values were 14.8%±1.8% for RU, 11.9%±4.0% for RM, 14.9%±2.3% for RL, 17.9%±2.9% for LU, and 15.1%±2.4% for LL. The actual decreasing rate of VC was overestimated in patients who underwent RU, RL, LU, and LL. In contrast, FEV1 was overestimated only in patients who underwent RL and LL. Patients with chronic obstructive pulmonary disease (COPD) exhibited significantly better preservation of FEV1. Conclusions: Patients scheduled for RL and LL, or those with COPD, appeared to exhibit preserved lung function in the late postoperative phase after pulmonary lobectomy.